ANALYSIS OF THE ACHIEVEMENT OF THE GLOBAL PURPOSE OF ELIMINATION OF CERVICAL CANCER IN UKRAINE - Rynhach, N.O.; Kuryk, O.G.; Hryhorchuk, S.P.; Dumytska, I.V.; Bazdyriev, K.V.; Myrvoda, S.S.; Bazdyriev, V.V. (World of Medicine and Biology, 2022)
Based on the analysis of the epidemiological situation in Ukraine, the study assesses the probability of achieving the purposes of the Global Strategy to accelerate the elimination of cervical cancer. Cervical cancer is a significant cause of death for Ukrainian women. In 2020, 30 % of all deaths were due to malignant neoplasms of the female genital organs, and approximately one in five deaths of women aged 30–45 years as a result of neoplasms was caused by cervical cancer. A comparative analysis with developed countries showed a higher probability of dying prematurely and a more significant contribution of the disease to the formation of the Global Burden of Disease indicator in young and old age. On the other hand, in Ukraine, there is a paradoxical phenomenon of decreasing mortality from cervical cancer with age. The COVID-19 pandemic was reflected in a decrease in the level of detection of new cases of the disease and an increase in the share of those detected in the advanced stage (in 2020 – 30.5 %, in 2021 – 31.1 % of deaths). It is suggested that there may be an increase in mortality due to untimely diagnosis and treatment of cervical cancer, which occurs against the background of a high prevalence of HIV infection, lower coverage of vaccination against human papillomavirus, and the low probability of Ukraine achieving the 90–70–90 goals by 2030.
Keywords: cervical cancer; neoplasms; age-related mortality; premature mortality